Emergency department preparation for COVID-19: accelerated care units. Issue 7 (27th May 2020) - Noble, Jeanne; Degesys, Nida Felicija; Kwan, Elizabeth; Grom, Edward; Brown, Cortlyn; Fahimi, Jahan; Raven, Maria
Abstract : By 11 February 2020 when the WHO named the novel coronavirus (SARS-CoV-2) and the disease it causes (COVID-19), it was evident that the virus was spreading rapidly outside of China. Although San Francisco did not confirm its first locally transmitted cases until the first week of March, our ED and health system began preparing for a potential COVID-19 surge in late February 2020. In this manuscript, we detail how the above responses were instrumental in the rapid deployment of two military-grade negative-pressure medical tents, named accelerated care units (ACU). We describe engagement of our workforce, logistics of creating new care areas, ensuring safety through personal protective equipment access and conservation, and the adaptive leadership challenges that this process posed. We know of no other comprehensive examples of how EDs have prepared for COVID-19 in the peer-reviewed literature. Many other EDs both in and outside of California have requested access to the details of how we operationalised our ACUs to facilitate their own planning. This demonstrates the urgent need to disseminate this information to our colleagues. Below we describe the process of developing and launching our ACUs as a potential model for other EDs around the country.